Respiratory virus testing and clinical outcomes among children hospitalized with pneumonia. Issue 9 (23rd June 2022) - Shapiro, Daniel J.; Thurm, Cary W.; Hall, Matthew; Lipsett, Susan C.; Hersh, Adam L.; Ambroggio, Lilliam; Shah, Samir S.; Brogan, Thomas V.; Gerber, Jeffrey S.; Grijalva, Carlos G.; Blaschke, Anne J.; Cogen, Jonathan D.; et al.
Abstract: Background: Despite the increased availability of diagnostic tests for respiratory viruses, their clinical utility for children with community‐acquired pneumonia (CAP) remains uncertain. Objective: To identify patterns of respiratory virus testing across children's hospitals prior to the COVID‐19 pandemic and to determine whether hospital‐level rates of viral testing were associated with clinical outcomes. Design, Setting, and Participants: Multicenter retrospective cohort study of children hospitalized for CAP at 19 children's hospitals in the United States from 2010‐2019. Main Outcomes and Measures: Using a novel method to identify the performance of viral testing, we assessed time trends in the use of viral tests, both overall and stratified by testing method. Adjusted proportions of encounters with viral testing were compared across hospitals and were correlated with length of stay, antibiotic and oseltamivir use, and performance of ancillary laboratory testing. Results: There were 46, 038 hospitalizations for non‐severe CAP among children without complex chronic conditions. The proportion with viral testing increased from 38.8% to 44.2% during the study period ( p < .001). Molecular testing increased (27.2% to 40.0%, p < .001) and antigen testing decreased (33.2% to 7.8%, p < .001). Hospital‐specific adjusted proportions of testing ranged from 10.0% to 83.5% and were not associated with length of stay, antibiotic use, or antiviral use. Hospitals that performed more viral testing did not have lower rates of ancillary laboratory testing. Conclusions: Viral testing practices varied widely across children's hospitals and were not associated with clinically important process or outcome measures. Viral testing may not influence clinical management for many children hospitalized with CAP.